Os efeitos do perdão de dívida sobre a apuração da contribuição ao PIS e da COFINS - Fernandes, Carlos Pacheco (2023)
presents Jesus of Nazareth’s life as a paradigm able to illuminate the mystery of human being, highlighting its dignity and its calling for humanization as criteria to social life.